Characterizing Spectral Channels of Visible Emission Line Coronagraph of Aditya-L1 - Patel, Ritesh; Megha, A.; Shrivastav, Arpit Kumar; Pant, Vaibhav; Vishnu, M.; Sankarasubramanian, K.; Banerjee, Dipankar (Frontiers in Astronomy and Space Sciences, 2021)
Aditya-L1 is India’s first solar mission with the Visible Emission Line Coronagraph (VELC), which consists of three spectral channels taking high-resolution spectroscopic observations of the inner corona up to 1.5 Rʘ at 5,303, 7,892, and 10,747 Å. In this work, we present a strategy for the slit width optimization of the VELC using synthetic line profiles by taking into account the instrument characteristics and coronal conditions for log(T) varying from 6 to 6.5. The synthetic profiles are convolved with simulated instrumental scattered light and noise to estimate the signal-to-noise ratio (SNR), which will be crucial to designing the future observation plans. We find that the optimum slit width for VELC turns out to be 50 μm, providing sufficient SNR for observations in different solar conditions. We also analyzed the effect of plasma temperature on the SNR at different heights in the VELC field of view for the optimized slit width. We also studied the expected effect of the presence of a CME on the spectral channel observations. This analysis will help to plan the scientific observations of VELC in different solar conditions.